194k views
15 votes
How do i factor n2 - n - 56

1 Answer

5 votes


{n}^(2) - n - 56 =


(n - 8)(n + 7)

_____________________________________________


a {x}^(2) + bx + c = 0


delta = {b}^(2) - 4ac


x(1) = ( - b + √(delta) )/(2a) \\


x(2) = ( - b - √(delta) )/(2a) \\

_____________________________________________


{n}^(2) - n - 56 = 0


delta = ({ - 1})^(2) - 4(1)( - 56)


delta = 1 + 224


delta = 225

Thus ;


n(1) = ( - ( -1) + √(225) )/(2 * 1) \\


n(1) = (1 + 15)/(2) \\


n(1) = (16)/(2) \\


n(1) = 8

And


n(2) = ( - ( - 1) - √(225) )/(2 * 1) \\


n(2) = ( 1 - 15)/(2) \\


n(2) = - (14)/(2) \\


n(2) = - 7

So


n(1) = 8


n(1) - 8 = 0 \: \: \: (\alpha )


n - 8 = 0 \: \: \: \: ( \alpha )

And


n(2) = - 7


n(2) + 7 = 0 \: \: \: \: \: ( \beta )


n + 7 = 0 \: \: \: \: ( \beta )

_____________________________________________


\alpha * \beta =


(n - 8)(n + 7)

User TsSkTo
by
5.2k points